Immediate Pre-Partum SARS-CoV-2 Status and Immune Profiling of Breastmilk: A Case-Control Study - Sánchez García, Laura; Gómez-Torres, Natalia; Cabañas, Fernando; González-Sánchez, Raquel; López-Azorín, Manuela; Moral-Pumarega, M. Teresa; Escuder-Vieco, Diana; Cabañes-Alonso, Esther; Castro, Irma; Alba, Claudio; Rodríguez Gómez, Juan Miguel; Pellicer, Adelina (Frontiers in Immunology, 2021)
Objetive To address the prevalence of SARS-CoV-2 and the evolutionary profile of immune compounds in breastmilk of positive mothers according to time and disease state. Methods Forty-five women with term pregnancies with confirmed non-severe SARS-CoV-2 infection (case group), and 96 SARS-CoV-2 negative women in identical conditions (control group) were approached, using consecutive sample. Weekly (1st to 5th week postpartum) reverse transcription polymerase chain reaction (RT-PCR) in nasopharyngeal swabs (cases) and breastmilk (cases and controls) were obtained. Concentration of cytokines, chemokines, and growth factors in breastmilk (cases and controls) were determined at 1st and 5th week post-partum. Results Thirty-seven (study group) and 45 (control group) women were enrolled. Symptomatic infection occurred in 56.8% of women in the study group (48% fever, 48% anosmia, 43% cough). SARS-CoV-2 RNA was not found in breastmilk samples. Concentrations of cytokines (IFN-γ, IL-1ra, IL-4, IL-6, IL-9, IL-13, and TNF-α) chemokines (eotaxin, IP-10, MIP-1α, and RANTES) and growth factors (FGF, GM-CSF, IL7, and PDGF-BB) were higher in breastmilk of the study compared with the control group at 1st week postpartum. Immune compounds concentrations decreased on time, particularly in the control group milk samples. Time of nasopharyngeal swab to become negative influenced the immune compound concentration pattern. Severity of disease (symptomatic or asymptomatic infection) did not affect the immunological profile in breast milk. Conclusions This study confirms no viral RNA and a distinct immunological profile in breastmilk according to mother’s SARS-CoV-2 status. Additional studies should address whether these findings indicate efficient reaction against SARS-CoV-2 infection, which might be suitable to protect the recipient child.